2015
DOI: 10.1097/mpa.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel Landscape Assessment in Pancreatic Ductal Adenocarcinoma

Abstract: Further studies are needed before endoglin replaces the conventional angiogenesis markers in PDCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Pancreatic ductal adenocarcinoma is a hypovascular and a hypoxic tumor. [25][26][27] This is confirmed in this study, since both the benign and malignant sites showed very low levels of mean blood volume (1.1% and 2.1%, respectively). These results are supported by a study of Erkan et al, 25 in which the microvascular density was determined: normal pancreas showed a five times higher microvascular density than fibrotic areas of chronic pancreatitis, and four times higher than pancreatic ductal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…Pancreatic ductal adenocarcinoma is a hypovascular and a hypoxic tumor. [25][26][27] This is confirmed in this study, since both the benign and malignant sites showed very low levels of mean blood volume (1.1% and 2.1%, respectively). These results are supported by a study of Erkan et al, 25 in which the microvascular density was determined: normal pancreas showed a five times higher microvascular density than fibrotic areas of chronic pancreatitis, and four times higher than pancreatic ductal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…It is notably upregulated in endothelial cells and has been considered to be a biomarker for tumor angiogenesis ( 12 ). The role of CD105 in the early metastasis of a tumor has gained attention, including in squamous cell carcinoma and pancreatic ductal adenocarcinoma ( 13 , 14 ). In RCC, the function of CD105 remains controversial ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microcirculatory maladjustment may lead to inadequate nutrients and oxygen supply, which results in consequential pancreatic dysfunction. 1 Emerging evidence confirms that pancreatic microcirculation profiles may serve as a determinant for variety of pathological conditions such as diabetes, 2 acute pancreatitis, 3 , 4 pancreatic cancer, 5 , 6 even hypertension, and obesity. 7 Therefore, the pancreatic microcirculation may herald, either as a marker or as a possible mechanism, the development of pancreatic-related diseases.…”
mentioning
confidence: 98%